Pengaruh Digital Marketing, Harga, dan Kreativitas Dekorasi Terhadap Minat Sewa Jasa MUA - Siti Robiah; Hendri Hermawan Adinugraha (JOURNAL ECONOMICS AND STRATEGY, 2022)
Today, the development of digital technology is very easy and fast. The strategy that can be done by entrepreneurs is to do marketing through social media, besides that price creativity and decoration are one of the considerations in increasing the success of a business. This study aims to determine the effect of digital marketing, price, and decoration creativity on interest in renting MUA services. The object of this research is the consumer of MUA services. The study used primary data by distributing questionnaires via google form. The data analysis technique used the analysis of the characteristics of the respondents, multiple linear regression analysis, partial test, simultaneous test, and the determinant coefficient. The results of the study have a coefficient of determination of 0.815. This means that the independent variable is very influential on the dependent variable by 82%, the remaining 18% is explained by other variables not examined.